Ab-initio calculations for the structural properties of Zr-Nb alloys - Kharchenko, V.O.; Kharchenko, D.O. (Condensed Matter Physics, 2013)
Ab-initio calculations for the structural properties of Zr-Nb alloys at different values of the niobium concentration are done at zero temperature. Different cases for Zr-Nb alloys with unit cells having BCC and HCP structures are considered. Optimal values of the lattice constants are obtained. Critical value for the niobium concentration corresponding to the structural transformation HCP → BCC at zero temperature is defined. Electronic densities of states for two different structures with niobium concentrations 12.5% and 25% having HCP and BCC structures, accordingly, are studied.